108k views
2 votes
Pleaseee, I really need help with this❤️

Pleaseee, I really need help with this❤️-example-1
User Ethyreal
by
6.4k points

1 Answer

1 vote

Answer:

(4x + 5)(4x - 3)

Explanation:

Given

16x² + 8x - 15

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 16 × - 15 = - 240 and sum = + 8

The factors are + 20 and - 12

Use these factors to split the x- term

16x² + 20x - 12x - 15 ( factor the first/second and third/fourth terms )

= 4x(4x + 5) - 3(4x + 5) ← factor out (4x + 5) from each term

= (4x + 5)(4x - 3) ← in factored form

User Benhatsor
by
5.8k points